2009
DOI: 10.1186/1756-9966-28-121
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer humoral immune response: involvement of Lewis y through the detection of circulating immune complexes and association with Mucin 1 (MUC1)

Abstract: Background: In cancer patients, MUC1 glycoprotein may carry Lewis y which could be involved in immune response. Purposes: 1-to evaluate the presence of Lewis y and MUC1 in circulating immune complexes (Lewis y/CIC and MUC1/CIC, respectively) and their correlation; 2-to analyze the possible presence of Lewis y in carbohydrate chains of tumoral MUC1 glycoprotein and 3-to correlate serum and tissue parameters considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
(39 reference statements)
1
9
0
Order By: Relevance
“…Cancers that are known to express Le Y include ovarian [185,190], breast [191], prostate [192], colon [193], and lung [194] cancers of epithelial cell origin [194]. Because the expression of Le Y in normal tissues is low and it is highly expressed in many cancers it is a good potential therapeutic target [194195].…”
Section: The Blood Group Lewis Related Tumor-associated Antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancers that are known to express Le Y include ovarian [185,190], breast [191], prostate [192], colon [193], and lung [194] cancers of epithelial cell origin [194]. Because the expression of Le Y in normal tissues is low and it is highly expressed in many cancers it is a good potential therapeutic target [194195].…”
Section: The Blood Group Lewis Related Tumor-associated Antigensmentioning
confidence: 99%
“…Larrain et al looked at the serum of breast cancer patients for circulating immune complexes of antibody to Le Y and the Le Y antigen expressed on Mucin1 (MUC1) [191]. The IgM Le Y circulating immune complex levels correlated with both IgM/IgG MUC1 and IgG Le Y circulating immune complex levels.…”
Section: The Blood Group Lewis Related Tumor-associated Antigensmentioning
confidence: 99%
“…19 It is considered that MUC1 is one of the molecules bearing the epitope sialyl Lewis x in cancer cells, 38 as well as other carbohydrate epitopes such as Lewis x and Lewis y. 39 In this report, a positive correlation between MUC1 versus Lewis x (r = 0.8830; P , 0.05) was found and also a tendency between MUC1 and Lewis x apical expression. These results indicate that MUC1 and Lewis x would be coexpressed, which would suggest that this mucin may be a Lewis x carrier.…”
Section: Normal Samplesmentioning
confidence: 67%
“…It can be carried by glycolipids, glycoproteins or mucins, and is highly expressed on a number of cancers of epithelial origin such as colon, [96] lung, [97] breast, [98] prostate [99] , and ovary. [100] It was reported that Le y expression in ovary tumor is relatively uniform compared to other glycolipids.…”
Section: Immunogenic Platforms For Taca Deliverymentioning
confidence: 99%